Analyser les effets socialisateurs des stratégies professionnelles déployées pour enseigner l’EPS à des élèves allophones nouvellement arrivé·es en France. - Anthony Forestier; Gaëlle Sempé; Gilles Combaz (Éducation et Socialisation)
The article highlights three professional strategies used by teachers to teach PE allophone students in the classrooms: observation through practical and collective immersion, personalized guidance through decomposed focus and affiliation with a French-speaking student. Deployed over nine months in a high school, an ethnographic survey combining observation (n = 300 hours) and interviews (n = 31), allowed us to capture and analyse the socializing effects of these strategies on the students surveyed. Our results show that although the teachers put in place, more or less intuitively, strategies to accompany allophone students in PE, this profile of students are not prepared to react in the same way, particularly with regard to their previous socialization. Situations of “blocking” are sometimes observed but must be contextualised with the ways of teaching of PE teachers and their pedagogical interest in integrating this group of pupils.